2009 nursing spectrum drug handbook - Schull, Patricia Dwyer 4 0 16; 5 (New York : McGraw-Hill Medical, 2009)
An A to Z nursing handbook that contains information on 3,000 brand-name and 1,000 generic drugs, with updates and revisions, advice on treating negative reactions to various medications, and warnings on hazardous drugs.
Includes bibliographical references (p. 1345-1346) and index.
Adult;Adult
Keywords: 2 -- 0; 6; Drugs;Pharmacology;Nursing;Medication errors;Drugs;Pharmacology;Nursing;Errors -- Handbooks, manuals, etc.;Handbooks, manuals, etc.;Handbooks, manuals, etc.;Handbooks, manuals, etc.;Handbooks, manuals, etc.;Handbooks, manuals, etc.;Handbooks, manuals, etc.;Handbooks, manuals, etc; 20; 2